Comparison of the effects of two antioxidant diets on oxidative stress markers in triathletes - Schneider, Claudia D.; Bock, Patricia M.; Becker, Georgia F.; Moreira, Jose Claudio F.; Bello-Klein, Adriane; Oliveira, Alvaro R. (Biology of Sport, 2018)
Intense exercise generates an imbalance in the redox system. However, chronic exercise can yield antioxidant adaptations. A few studies with humans have investigated the effects of antioxidant diets on athletes. Therefore we compared the effects of two dietary interventions on oxidative stress in competitive triathletes. Thirteen male triathletes were selected and divided into 2 groups: one that had a regular antioxidant diet (RE-diet) and the other that had a high antioxidant diet (AO-diet). The diet period was 14 days and blood samples were collected before and after this period. The AO-diet provided twice the dietary reference intake (DRI) of α-tocopherol (30 mg), five times the DRI of ascorbic acid (450 mg), and twice the DRI of vitamin A (1800 g), while the RE-diet provided the DRI of α-tocopherol (15 mg), twice the DRI of ascorbic acid (180 mg) and the DRI of vitamin A (900 μg). The oxidative stress parameters evaluated were: thiobarbituric acid reactive substances (TBARS), total reactive antioxidant potential (TRAP), total sulfhydryl, carbonyl, superoxide dismutase (SOD) activity, hydrogen peroxide consumption and glutathione peroxidase (GPx) activity. We observed, after the diet period, an increase in sulfhydryl, TRAP, TBARS and SOD activity, and a decrease in carbonyl levels. However, no changes were found in hydrogen peroxide consumption or GPx activity. We concluded that antioxidant-enriched diets can improve the redox status of triathletes.